Accessing valley degree of freedom in bulk Tin(II) sulfide at room temperature - Shuren Lin (Nature Portfolio, 2018)
Valleytronics leverages the valley degree of freedom to engineer light-matter interaction. Here, the authors demonstrate a room temperature, bias-free valley effect in bulk SnS by means of spectroscopic measurements, previously unattainable using atomically thin transition metal dichalcogenides.